Ultramicroporous Carbons Puzzled by Graphene Quantum Dots: Integrated High Gravimetric, Volumetric, and Areal Capacitances for Supercapacitors. (31st October 2018) - Zhang, Su; Zhu, Jiayao; Qing, Yan; Wang, Luxiang; Zhao, Jing; Li, Jing; Tian, Wenhui; Jia, Dianzeng; Fan, Zhuangjun
Abstract: Porous carbons integrated with high gravimetric/volumetric/areal capacitances, especially at high mass loadings (>10 mg cm −2 ), are important for practical applications in supercapacitors. Here, a strategy is developed for the synthesis of ultramicroporous carbons puzzled by graphene quantum dots as the building units through chemical welding and in situ activation. The resulted carbon has unique ultramicroporous structure (≈0.5 nm) with both high surface area (1730 m 2 g −1 ) and packing density (0.97 g cm −3 ), providing high gravimetric and volumetric capacitances of 270 F g −1 and 262 F cm −3 at 1 A g −1, respectively. More importantly, such carbon achieves an ultrahigh areal capacitance of 5.70 F cm −2 with a high mass loading of 25 mg cm −2 at 1 A g −1, which is one of the best among the previously reported porous carbons. Furthermore, a two‐electrode supercapacitor exhibits an ultrahigh areal capacitance of 3 F cm −2 at 0.5 A g −1, rapid charge–discharge ability, and long lifespan. This work paves an avenue for developing advanced porous carbons with integrated capacitive performances for supercapacitors. Abstract : Ultramicroporous carbon with both high specific surface area (1730 m 2 g −1 ) and packing density (0.97 g cm −3 ), constructed using graphene quantum dots as building units, shows integrated high gravimetric/volumetric/areal capacitances as well as excellent rate performance and cycling stability.